The impact of extreme weather on temporary work absence - Nekeisha Spencer; Mikhail-Ann Urquhart (International Labour Organization (ILO), 2021)
The study examines the impact that extreme weather has on temporary work absence in Jamaica, a central concern given the country's negative experience with such events. The study uses quarterly data containing key labour market indicators on an unbalanced panel of individuals along with climatic data for the period 2004 to 2014. The findings are several. Firstly, neither excess rainfall nor hurricane affects the odds of being temporarily absent from work. However, including interactions between these weather variables and other key labour market indicators show that only excess rainfall increases the odds of being temporarily absent from work. Secondly, the estimated increase due to excess rainfall translates into a probability of 0.002 per cent of being temporarily absent. Although very marginal, this estimated outcome of excess rainfall is plausible given that workers may be unable to navigate flooded roads to attend work or perhaps are confined due to unforeseen conditions arising in their home environment. Thirdly, using compensation of salaried employees which includes salaries and benefits, we calculated that the average estimated cost of temporary daily absence from work to the labour market is approximately US2.81. The estimated results and losses, though negligible, can possibly have implications for the labour market which may involve developing e-commuting policies to combat these unfavourable outcomes. The absence of an impact as it relates to hurricanes possibly indicates that existing mechanisms are working to mitigate storm impacts, or the closure of workplaces due to disruptions in the economy from storm occurrences, results in no work.
Keywords: 330; labour force participation; unemployment; leave of absence; labour legislation; natural disasters; statistics